2021
DOI: 10.22159/ijcpr.2021v13i4.42733
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Significance of Novel Coumarins: A Review

Abstract: Coumarone is a chemical compound found in many plants. Coumarone having diverse pharmacological properties popularly known as an antimicrobial, Analgesic anti-inflammatory, Anticancer, Antiviral, anticoagulant, antihypertensive, anticonvulsant, antihyperglycemic, antioxidant, activities. Coumarone was also observed in all green color veggies, and also in fruits and their seeds, dark coffee, tea leafs, further it is used for herbal remedies due to having less toxicity, very cheaper. The most useful method for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Additionally, pyrimidine derivatives have been identified to have properties, which were similar to those of antibiotics, such as: bacimethrin (5-hydroxymethyl-2-methoxypyrimidine-4-amine) derivative is effective against some infections caused by staphylococci. Cytosine derivatives has been reported to be resistant against mycobacteria and some Gram-positive and Gram-negative bacteria [32]. Additionally, uracil derivatives also had the anti-oxidant ability based on the assay of DPPH free radical scavenging (5aminouracil (IC50: 3 mg/mL), 5-amino-6-methyluracil (IC50: 5 mg/mL), and 5-hydroxy-6-methyluracil (IC50: 15 mg/mL) [34].…”
Section: Thin-layer Chromatography Analysis Of the Purified Anti-mrsa...mentioning
confidence: 99%
“…Additionally, pyrimidine derivatives have been identified to have properties, which were similar to those of antibiotics, such as: bacimethrin (5-hydroxymethyl-2-methoxypyrimidine-4-amine) derivative is effective against some infections caused by staphylococci. Cytosine derivatives has been reported to be resistant against mycobacteria and some Gram-positive and Gram-negative bacteria [32]. Additionally, uracil derivatives also had the anti-oxidant ability based on the assay of DPPH free radical scavenging (5aminouracil (IC50: 3 mg/mL), 5-amino-6-methyluracil (IC50: 5 mg/mL), and 5-hydroxy-6-methyluracil (IC50: 15 mg/mL) [34].…”
Section: Thin-layer Chromatography Analysis Of the Purified Anti-mrsa...mentioning
confidence: 99%
“…agonistic, mitotic kinesin inhibiting, antibacterial, fungicidal, etc. 70 Dankers et al reported two conventional methods for the modification of peptides by ureidopyrimidinone (UPy) moieties on the solid support. 71 In the first method, peptides were modified with UPy units at the N-terminal amino acid.…”
Section: Pyrimidinesmentioning
confidence: 99%
“…Coumarin represents a core structural motif which is widely present in natural products and synthetic pharmaceuticals . Therefore, their synthesis and functionalization have given rise to much interest from the synthetic community over the past decades .…”
Section: Introductionmentioning
confidence: 99%